Impact Of Mergers And Acquisitions On Operational Performance Of Islamic Banking Sector - Nazim Ullah; Fauzias Mat Nor; Junaidah Abu Seman (EScience Press, 2024)
Merger and acquisition (hereafter M&A) are the business expansion strategy. Islamic bank is the niche banking sector compared to its peers while it is categorized as too small to succeed. The paper aims to analyze the impact of M&A on the operational performance of the Islamic banking sector. This study employs empirical research methods, namely cross-sectional pooled regression and panel data regression to analyze a set of samples consisting of 10 Islamic banks involved in M&A from 6 countries, drawn from the International Monetary Fund (IMF), World bank, Ficth Connect, and Bloomberg over the years of 2009Q1to 2018Q4. The operational performance is estimated using accounting-based measures while the Herfindahl-Hirschman Index (HHI) and the concentration ratio (CR) are applied to signify market structure. Total assets, total deposits, and operating income variables are used to represent bank size. The findings indicate that bank size shows a negative impact on operational performance. While the segregated level of bank size which is larger banks and concentrated market structure has a greater impact on the operational performance of Islamic banks in the post-M&A period. The paper concludes by discussing policy implications for policymakers and academicians for having the strategic decision on the M&A deal and further research.